PROFESSIONAL PREPARATION TRAININGS IN THE FUTURE UP SOCIAL WORKERS - Котикова, Олена Михайлівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
Article consecrated Rationale system trenning As sredstva Preparation of the future Up Social workers, by ananlyzyruet Various approaches for Understanding psychological essence trenning trenynhovыh and technology in general, s Opportunities and limitations in uchebnom Using a process, suschestvuyuschuyu s practice during the preparation Implementation future Up Social workers. Need to Aktsentyruetsya creation system trenning psychological and Increase in the preparation rolls s future managers sotsyalnoy areas